EVALUATION OF IMMUNOMODULATORY EFFECT OF T-AYU-HM PREMIUM IN EXPERIMENTAL ANIMAL MODELS (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
To evaluate the immunomodulatory effect of T-AYU-HM Premium in experimental animal models. Female Wistar rats were divided into four groups in each model and acclimatized under standard conditions. The control group received vehicle (0.5% CMC), the standard group received Levamisole (50 mg/kg), Test-1 group received T-AYU-HM Premium (600 mg/kg), and Test-2 group received T-AYU-HM Premium (1200 mg/kg). The effect of T-AYU-HM Premium as an immunomodulator was studied by evaluating the neutrophil adhesion model, carbon clearance model, cyclophosphamide-induced neutropenia model, and haemagglutinating antibody titer model. The neutrophil adhesion in standard, Test-1, and Test-2 are 55.39%, 23.32%, and 38.06%, respectively. The %reduction of TLC and DLC in standard and both test groups were significant compared to the control group after nylon fiber treatment. The phagocytic index of standard, test-1 and test-2 was found to be 0.01735, 0.01416, and 0.00923, respectively, this indicates that the test drug affects the reticuloendothelial system. A significant decrease in cyclophosphamide-induced neutropenia implies that the cyclophosphamides’ influence on the hemopoietic system is lessened. The percentage reduction in TLC of standard and both test drug groups are 11.12%, 20.66%, and 13.43%, respectively. The %reduction in DLC of standard and both test drug groups were significant compared to a control group. Haemagglutinating antibody (HA) titer test determines the effect of the drug on humoral immunity. Primary HA titer values of standard, test-1 and test-2 were 5.33, 2.66, and 4.50, respectively. Secondary HA titer values of standard, test-1, and test-2 were 13, 7.16, and 11.16, respectively. HA titer value significantly increases in standard and test groups compared to control in both primary and secondary evaluation. In the current study, results show that the T-AYU-HM Premium tablets exhibit Immunomodulatory activity.